Social Media Impact Analysis on the Use of Indonesian in Class IX of SMP Negeri 35 Medan - Rosmaini, Rosmaini; Ramadhani, Anisa; Atthoyibah, Assyifa'u Qolbiatu; Siregar, Mutia Haryani; Priska, Nadia; Ramadhani, Suci (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Social media has become an integral part of teenagers' lives, including its influence on the use of the Indonesian language. This study aims to analyze the impact of social media usage on language development among ninth-grade students at SMPN 35 Medan. The research employs a quantitative survey approach, involving 23 students as respondents. Data were collected through questionnaires and analyzed descriptively. The findings indicate that most students use social media daily, affecting their language habits. While some students strive to maintain proper Indonesian usage, there is an increasing tendency to use slang and abbreviations in daily communication. Additionally, some students struggle to use standard Indonesian due to the influence of social media. This study concludes that social media significantly impacts students' language habits, both positively and negatively. Therefore, educational strategies are needed to raise awareness among students about the importance of using proper Indonesian in various contexts.